Optimization of an Injectable Hydrogel Depot System for the Controlled Release of Retinal-Targeted Hybrid Nanoparticles - Ilaria Ottonelli; Andrea Bighinati; Elisa Adani; François Loll; Riccardo Caraffi; Maria Angela Vandelli; Frank Boury; Giovanni Tosi; Jason Thomas Duskey; Valeria Marigo; Barbara Ruozi (MDPI AG, 2022)
A drawback in the development of treatments that can reach the retina is the presence of barriers in the eye that restrain compounds from reaching the target. Intravitreal injections hold promise for retinal delivery, but the natural defenses in the vitreous can rapidly degrade or eliminate therapeutic molecules. Injectable hydrogel implants, which act as a reservoir, can allow for long-term drug delivery with a single injection into the eye, but still suffer due to the fast clearance of the released drugs when traversing the vitreous and random diffusion that leads to lower pharmaceutic efficacy. A combination with HA-covered nanoparticles, which can be released from the gel and more readily pass through the vitreous to increase the delivery of therapeutic agents to the retina, represents an advanced and elegant way to overcome some of the limitations in eye drug delivery. In this article, we developed hybrid PLGA-Dotap NPs that, due to their hyaluronic acid coating, can improve in vivo distribution throughout the vitreous and delivery to retinal cells. Moreover, a hydrogel implant was developed to act as a depot for the hybrid NPs to better control and slow their release. These results are a first step to improve the treatment of retinal diseases by protecting and transporting the therapeutic treatment across the vitreous and to improve treatment options by creating a depot system for long-term treatments.